Índice de multifuncionalidad de la agricultura familiar campesina (IMAFC): Caso municipio de Calpan, Puebla. - Blanca Bautista, Martina; Ocampo Fletes, Ignacio; Juárez Sánchez, José Pedro; Herrera-Cabrera, Braulio Edgar; Pérez Ramírez, Efraín; Sánchez Morales, Primo (Revista de Geografía Norte Grande, 2024)
Peasant farming systems are multifunctional, since their culture-based structure generates different environmental, social and economic functions. However, agricultural modernization and the change from agricultural to urban zones have caused the loss of multifunctionality in these systems. Therefore, the objective of this study was to generate a peasant family farming multifunctionality index for the municipality of Calpan, Puebla. A survey was conducted to gather information and the instrument was a questionnaire applied to a sample of 81 producers. A peasant family farming multifunctionality index (PFFMI) was generated, made up of four fields: sociocultural, environmental, economic and territorial; four general functions, 12 specific ones, and 17 indicators. The results show a PFFMI of 72.61, corresponding to category IV, medium high, with outstanding functions such as: conservation of knowledge, maintenance of agricultural biodiversity, conservation of agroecological practices, consolidation of food security, promotion of job generation, support of landscapes configurations, and rootedness of the territory. The study concludes that peasant family farming maintains a high functionality.